The Role of RECK in Hepatobiliary Neoplasia Reveals Its Therapeutic Potential in NASH - Dashek, Ryan J.; Diaz, Connor; Chandrasekar, Bysani; Rector, R. Scott (Frontiers in Endocrinology, 2021)
Non-alcoholic fatty liver disease (NAFLD) is a multimorbidity disorder ranging from excess accumulation of fat in the liver (steatosis) to steatohepatitis (NASH) and end-stage cirrhosis, and the development of hepatocellular carcinoma (HCC) in a subset of patients. The defining features of NASH are inflammation and progressive fibrosis. Currently, no pharmaceutical therapies are available for NAFLD, NASH and HCC; therefore, developing novel treatment strategies is desperately needed. Reversion Inducing Cysteine Rich Protein with Kazal motifs (RECK) is a well-known modifier of the extracellular matrix in hepatic remodeling and transition to HCC. More recently, its role in regulating inflammatory and fibrogenic processes has emerged. Here, we summarize the most relevant findings that extend our current understanding of RECK as a regulator of inflammation and fibrosis, and its induction as a potential strategy to blunt the development and progression of NASH and HCC.